The Hygiene Factors Contributing to Work Satisfaction, Interaction with locals and Life Satisfaction among Dell Expatriates in the Asia Pacific Region - Suhartini, Nining (2012)
Pembangunan profesional ekspatriat telah menjadi semakin penting kepada organisasi transnasional sejak beberapa dekad yang lalu (Adler, 2008; Mendenhall, 2006; Mezias & Scandura, 2005).